The Financial Implications of Tobacco Pricing in the European Union Countries - Rafal Rosinski (Communications of International Proceedings, 2023)
This study examines the fiscal implications of tobacco taxation in European Union (EU) nations, focusing on its impact on budgetary revenue. Utilizing official reports from the European Commission and the World Health Organization (WHO), the empirical analysis reveals that higher excise taxes on tobacco significantly contribute to total tax revenue, particularly in EU member states where tobacco prices are comparatively lower. Notably, 'old EU' countries tend to impose higher average tax rates on cigarettes, while 'new EU' nations demonstrate a higher overall tax burden when considering the share of taxes embedded in the cigarette prices. The findings suggest a pattern of tax harmonization, leading to a substantial upsurge in tobacco taxation for new EU members, with future prospects indicating further convergence in tobacco tax policies.
Keywords: Excise tax; tax harmonization; price tobacco; budget revenue